2019
DOI: 10.5195/jyd.2019.662
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination Through Circus Arts: Exploring Youth Development in a Novel Activity Context

Abstract: Youth development takes place in many contexts, with different resulting participant outcomes. Broadening the scope of research to include non-traditional contexts such as youth circus arts programs, which are both similar to and different from other out-of-school-time contexts, may promote better understanding of the ways in which these programs impact youth development. The present study examined the prevalence of support for basic psychological needs and positive developmental outcomes among youth circus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Perceived competence toward exercise programs was assessed using the five items from the perceived competence subscale of the Intrinsic Motivation Inventory ( McAuley et al, 1989 ), which has been previously used in elementary physical education and other youth program settings ( Standage et al, 2005 ; Agans et al, 2019 ). An example item is “When it comes to playing physically active games, I think I am pretty good,” and the response scale ranged from 1 (“strongly disagree”) to 5 (“strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived competence toward exercise programs was assessed using the five items from the perceived competence subscale of the Intrinsic Motivation Inventory ( McAuley et al, 1989 ), which has been previously used in elementary physical education and other youth program settings ( Standage et al, 2005 ; Agans et al, 2019 ). An example item is “When it comes to playing physically active games, I think I am pretty good,” and the response scale ranged from 1 (“strongly disagree”) to 5 (“strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…With many schools failing to nurture self-determination (Tough, 2016), community-based youth development programs can support youth success in school and other domains by helping them navigate the process of motivational internalization. Accordingly, some after-school programs (Berry & LaVelle, 2013;Grolnick et al, 2007), recreation camps (Hill & Sibthorp, 2006), youth activism programs (Dawes & Larson, 2011), youth enrichment programs (Martin, 2005), and circus arts programs (Agans et al, 2019) have explicitly emphasized SDT as a motivational construct. Dawes and Larson's (2011) study of diverse youth programs indicates that even if youth are extrinsically motivated to participate at the start, it is possible to enhance their psychological engagement through their experiences in the program.…”
Section: Organismic Integration Theory: Internalizing Extrinsic Motivmentioning
confidence: 99%
“…Akiva and colleagues (2014) affirm that involving adolescent youth in decision-making processes can enhance their motivation to participate in development programs. Some of these programs, however, focus specifically on enhancing intrinsic motivation rather than by internalizing externally regulated motivation (Agans et al, 2019). Also, whether focused on school-or community-based settings, many studies of self-determination use single-point-intime measurements (Agans et al, 2019;Standage et al, 2006;van Egmond et al, 2020).…”
Section: Organismic Integration Theory: Internalizing Extrinsic Motivmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Circus is uniquely positioned for use as a health intervention due to its huge variety, non-competitive environment, and unique, fun nature. [2][3][4] Circus activities also align with the development of fundamental movement skills 5 and physical literacy, 3 and are thus well suited for use in children, youth and adolescent populations (defined as up to 24 years). 6,7 In addition, a study by Maglio and McKinstry 8 found that circus activities are congruent with criteria such as physical health, social connectedness, teamwork, and belonging, which are often development goals in educational settings.…”
Section: Introductionmentioning
confidence: 99%